Relationship between Knowledge and Attitude of Healthy Living with Healthy Behavior Patterns in Medical Students - Angga Putra Surya Rahmadhani; Dorta Simamora; Sukma Sahadewa (Universitas Wijaya Kusuma Surabaya, 2023)
Medical students play an important role in promoting health because they are prospective doctors. Medical students are considered students who have sufficient knowledge and skills about a healthy lifestyle and have a positive attitude towards health. In fact, there are still many medical students who have not implemented a healthy lifestyle. The purpose of this study was to determine the relationship between knowledge and healthy living attitudes with healthy living behavior patterns in FK–UWKS students class 2018. The study used an observational quantitative approach with a cross-sectional study design with 150 respondents taken using the census method (total sampling). analysis technique using spearman rank test. The results showed that the level of knowledge of healthy living was quite high at 78.1% and positive attitudes about healthy living was 54.7%, while having unhealthy behavior patterns was 92.2%. The Spearman rank test showed that there was a relationship between knowledge of healthy living with healthy living behavior patterns p = 0.000 and a healthy lifestyle also had a relationship with healthy lifestyle behaviors p = 0.000. The conclusion of this study is that the pattern of healthy living behavior is not only influenced by knowledge but also by a healthy attitude.